Act Naturally: Francis Ponge's Morals and Measures of Human Nature - Hugh Hochman (Studies in 20th & 21st Century Literature, 2021)
This article explores how a poetics of the nonhuman in the work of Francis Ponge underwrites a humanism wherein we no longer have to take sides in the conflict between the linguistic projects that tend toward subordination or comprehension of the nonhuman and the resistance that the nonhuman endlessly opposes to these projects. Close readings of texts that figure the defeat of reason in its linguistic expression of the nonhuman, as well as texts that figure human comportment in nonhuman tropes, reveal an ethical project of human well-being acting in agreement with its nature.
Keywords: Francis Ponge; French poetry; 20th-century poetry; ethics; rhetoric; fable; poetry and philosophy; Aristotle; rhetoric of example; poetics of the object; nonhuman; human and nature